Delivery of Active Medical Management without Dialysis through an Embedded Kidney Palliative Care Model. Issue 11 (24th November 2022) - Bursic, Alexandra E.; Schell, Jane O.; Ernecoff, Natalie C.; Bansal, Amar D.
Key Points: Integrating palliative care into kidney care can lead to improvements in symptom management, advance care planning, and hospice utilization. An embedded kidney palliative care model can enable delivery of active medical management without dialysis to patients whose values align with forgoing dialysis. Visual Abstract: Abstract : Background: Patients with CKD have high symptom burden, low rates of advance care planning (ACP), and frequently receive care that is not goal concordant. Improved integration of palliative care into nephrology and access to active medical management without dialysis (AMMWD) have the potential to improve outcomes through better symptom management and enhanced shared decision making. Methods: We describe the development of a kidney palliative care (KPC) clinic and how palliative care practices are integrated within an academic nephrology clinic. We performed a retrospective electronic health record (EHR) review for patients seen in this clinic between January 2015 and February 2019 to describe key clinical activities and delivery of AMMWD. Results: A total of 165 patients were seen in the KPC clinic (139 with CKD and 26 who were already receiving dialysis). Fatigue, mobility issues, and pain were the three most prevalent symptoms (85%, 66%, 58%, respectively). Ninety-one percent of patients had a surrogate decision maker documented in the EHR; 87% of patients had a goals-of-care conversation documented in the EHR. Of the 139 patients with CKD, 67 (48%) chose AMMWD as their disease progressed. Sixty-eight percent (41 of 60) of patients who died during the study were referred to hospice. Conclusions: Our findings suggest that the integration of palliative care into nephrology can assist in identification of symptoms, lead to high rates of ACP, and provide a mechanism for patients to choose and receive AMMWD. The percentage of patients choosing AMMWD in our study suggests that increased shared decision making may lower rates of dialysis initiation in the United States. Additional prospective research and registries for assessing the effects of AMMWD have the potential to improve care for people living with CKD.